1986
DOI: 10.1139/v86-148
|View full text |Cite
|
Sign up to set email alerts
|

Hydridoiridium(III) sulfoxide complexes and their reactivity toward dioxygen

Abstract: , and PAL KVINTOVICS. Can. J. Chem. 64, 897 (1986). Synthetic routes to hydridoiridium(II1) dimethylsulfoxide complexes via oxidative addition of HCl or Hz to precursor in situ iridium(1) species are described. The complexes, tran~,mer-IrHCl~(DMSO)~ (la) and ci~,rner-IrH~Cl(DMSO)~ (2), have been characterized by 'H nrnr and ir, and contain only S-bonded sulphoxide, DMSO. Comparison is made with data for other isomers reported in the literature, and some discrepancies are discussed. The decomposition of l a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…405 Later, James and co-workers reported that the decomposition of trans-IrCl 2 H-(dmso-S) 3 in chloroform led to a mixture of the two linkage isomers mer-IrCl 3 (dmso-S) 3 (53) and mer,cisIrCl 3 (dmso-S) 2 (dmso-O) (54) (Chart 33), while decomposition of the dihydride cis,mer-IrH 2 Cl(dmso-S) 3 led to 53 exclusively. 406 It should be noted, though, that these neutral species were not isolated, but identified only in solution by NMR spectroscopy. 406 A neutral Ir(III)-dmso species containing metalated benzylacetophenone, cis,cis-IrCl 2 (dmso-S) 2 (PhCO-(CH 2 )CHPh), was isolated in small amounts during the hydrogenation of benzylideneacetophenone by propan-2-ol catalyzed by 51 and was structurally characterized by X-ray diffraction.…”
Section: Iridium−halide−dmso Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…405 Later, James and co-workers reported that the decomposition of trans-IrCl 2 H-(dmso-S) 3 in chloroform led to a mixture of the two linkage isomers mer-IrCl 3 (dmso-S) 3 (53) and mer,cisIrCl 3 (dmso-S) 2 (dmso-O) (54) (Chart 33), while decomposition of the dihydride cis,mer-IrH 2 Cl(dmso-S) 3 led to 53 exclusively. 406 It should be noted, though, that these neutral species were not isolated, but identified only in solution by NMR spectroscopy. 406 A neutral Ir(III)-dmso species containing metalated benzylacetophenone, cis,cis-IrCl 2 (dmso-S) 2 (PhCO-(CH 2 )CHPh), was isolated in small amounts during the hydrogenation of benzylideneacetophenone by propan-2-ol catalyzed by 51 and was structurally characterized by X-ray diffraction.…”
Section: Iridium−halide−dmso Complexesmentioning
confidence: 99%
“…406 It should be noted, though, that these neutral species were not isolated, but identified only in solution by NMR spectroscopy. 406 A neutral Ir(III)-dmso species containing metalated benzylacetophenone, cis,cis-IrCl 2 (dmso-S) 2 (PhCO-(CH 2 )CHPh), was isolated in small amounts during the hydrogenation of benzylideneacetophenone by propan-2-ol catalyzed by 51 and was structurally characterized by X-ray diffraction. 409 The group of Milstein has recently reported the preparation of two novel Ir(I)-dmso complexes, IrCl-(dmso-S) 3 (55) led to the isolation of the chloro-bridged dimer [(dmso-S) 2 Ir(µ-Cl) 2 Ir(dmso-S) 2 ] (57).…”
Section: Iridium−halide−dmso Complexesmentioning
confidence: 99%
“…NMR spectrum for the reaction between 1 and 2-propanol in CDCl3 (verified by passing gaseous H2 through the same sample). Additionally, the formation of trace amounts of CHDCl2 was detected in CDCl3 solutions as a characteristic pattern of three lines of equal intensity centered at δ 5.33, resulting from the spin-spin coupling between proton and deuterium nuclei.The genesis of H2 and CHDCl 2 under these conditions could be ascribed to the formation of a short-lived metal hydride species[26]. The effect of deuterium substitution in the alcohol molecule was investigated to determine the source of the transferred hydrogen atom, through comparison of the reaction rates of 1 with 2-propanol vs (CD 3 ) 2 CD-OD[27].…”
mentioning
confidence: 99%
“…On the basis of the results presented above, we proposed the mechanism displayed in Scheme for the vinylsilane homocoupling reaction . Initially, cyclooctene in the iridium(I) complex 2 undergoes exchange with vinylsilane to generate the corresponding vinylsilane-coordinated iridium(I) complex 5 , which then is protonated by HCl to produce the β-silylethyliridium(III) complex 7 via the intermediacy of hydridoiridium(III) complex 6 . The silylethyl group in 7 undergoes migratory insertion into the vinylsilane ligand through a carbometallation process to give 2,4-disilylbutyliridium(III) complex 8 .…”
mentioning
confidence: 99%
“…Polymer 13a ( n = 2) was degraded by using perfluoro-hexyl iodide/BEt 3 -promoted iodine atom transfer radical addition followed by atom transfer cleavage with BEt 3 /H 3 PO 2 /pyridine as described above (Scheme a). This reaction leads to selective carbon–silicon bond cleavage to give α-perfluoroalkyl ketone 14 and the unstable silanol 15 , which dimerizes to form siloxane 16 .…”
mentioning
confidence: 99%